What are the health risks of using insulin in patients with type 2 diabetes?. Issue 4 (April 2017) - Kiani, Sarah; Hanif, Mohammad Yusuf; Somma, Lorenzo; Achkar, Morhaf Al
Abstract : EVIDENCE‐BASED ANSWER : Despite its effectiveness in improving blood sugar control, high‐intensity insulin use is associated with more episodes of hypoglycemia (SOR: A, systematic review of RCTs). Compared with sulfonylureas plus metformin, insulin plus metformin is associated an excess of 11 deaths per 1, 000 person‐years (SOR: B, retrospective cohort). The evidence is conflicting about an association between insulin use and colorectal cancer (no SOR given).